ANALISIS TEORI PERTENTANGAN KELAS KARL MARX DI ERA REVOLUSI INDUSTRI 4.0 TERHADAP KETENAGAKERJAAN DI INDONESIA (JEB17 : Jurnal Ekonomi dan Bisnis, 2023)
This study discusses the industrial revolution 4.0 as an industrial revolution that implicates the internet, information, and communication technology in it. The research was written using the literature review research method which was presented descriptively. Meanwhile, the data source presented comes from relevant reading sources. The results of this study are that the industrial revolution 4.0 provides its advantages and challenges in its application, including problems in the workforce. Employment or labor in the era of the industrial revolution 4.0 made Karl Marx's theory of class conflict continue to last because of the inability of workers to improve their capabilities which resulted in the alienation of the workers. Keywords: Karl Marx Class Conflict, Industrial Revolution 4.0, Employment